เตรียมเสบียงไว้เลี้ยงตัว เล่ม 1 - Paphaso, Phramaha VIroch; Leeka, Jaras (Journal of Graduate MCU KhonKaen Campus, 2023)
This book review is for presenting food supplies. By understanding how to live with carelessness it is mindful in the present moment by refraining from doing evil, doing good deeds, and purifying the mind. Because karma will lead us to a new realm if a person does any karma, by body, speech, and mind, that karma will belong to that person. In addition, follow him like a shadow and this karma will depend on the creatures in the next world, so it is necessary to prepare provisions that are merit in order to provide provisions for the next world.